2022
DOI: 10.1186/s12866-022-02556-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Paenarthrobacter ureafaciens ZF1 on the soil enzyme activity and microbial community during the bioremediation of atrazine-contaminated soils

Abstract: Bioremediation of atrazine-contaminated soil is considered a safe and effective approach in removing contaminates from the soil. However, the effects of adding foreign organisms to assist bioremediation on soil environmental quality and ecosystem are unclear. Here, the ecological remediation potential of strain Paenarthrobacter ureafaciens ZF1 on atrazine-contaminated soil was investigated through miniature experiments using variations in soil enzymes and bacterial communities as indicators. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Bacteria, ubiquitous microorganisms inhabiting diverse environments, play an indispensable role in shaping the biosphere and influencing human health [ 1 – 3 ]. Their sheer abundance and diversity underscore their significance in ecological processes, ranging from nutrient cycling to bioremediation [ 4 6 ]. Moreover, bacteria have been central to pivotal discoveries in the fields of genetics, molecular biology, and biotechnology, serving as model organisms for fundamental biological research.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria, ubiquitous microorganisms inhabiting diverse environments, play an indispensable role in shaping the biosphere and influencing human health [ 1 – 3 ]. Their sheer abundance and diversity underscore their significance in ecological processes, ranging from nutrient cycling to bioremediation [ 4 6 ]. Moreover, bacteria have been central to pivotal discoveries in the fields of genetics, molecular biology, and biotechnology, serving as model organisms for fundamental biological research.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, our previous study showed that Actinomycetota are major contributors to Rhizoctonia solani inhibition in soil ( 28 ), and from Rhizoctonia -suppressive soil, we isolated Paenarthrobacter ureafaciens , which belongs to the Actinomycetota phylum ( 29 , 30 ). P. ureafaciens is known as an indole acetic acid and siderophore producer ( 31 ) as well as an herbicide-degrading bacterium ( 32 , 33 ). Thus, Actinomycetota P. ureafaciens may impact plant growth and microbial communications in soil.…”
Section: Introductionmentioning
confidence: 99%